Characterization of meat quality, storage stability, flavor-related compounds, and their relationship in Korean Woorimatdag No. 2 chicken breast meat during cold storage - Yousung Jung; Soomin Oh; Sangrok Lee; Hee-Jeong Lee; Hyo-Jun Choo; Cheorun Jo; Ki-Chang Nam; Jun-Heon Lee; Aera Jang (Poultry Science)
We evaluated the quality, storage stability, and flavor-related compounds of breast meat from a novel Korean native chicken breed (Woorimatdag No. 2; WRMD2) and commercial broiler (CB) during seven days of aerobic cold storage. We found that pH and drip loss increased gradually during storage and WRMD2 exhibited a significantly lower pH and higher drip loss than CB. In both groups, aerobic plate counts, volatile basic nitrogen, and lipid oxidation levels increased, whereas creatine and dipeptide levels gradually decreased during storage. WRMD2 exhibited a significantly higher anserine content and lower carnosine-to-anserine ratio than CB. Flavor nucleotide content was influenced more by the storage period, whereas fatty acid composition was affected more by genetic differences. WRMD2 exhibited significantly higher levels of polyunsaturated fatty acids, especially C20:4n6 and C22:6n3, than CB. Interestingly, multivariate analysis highlighted several volatile compounds, including methyl salicylate (day 1), dodecanal (day 3), naphthalene (day 5), and 2,4-decadienal (day 7) as potential biomarkers to distinguish between WRMD2 and CB on each storage day. Correlation analysis identified five key meat quality traits, including drip loss, aerobic plate counts, and anserine that are strongly associated with flavor substances, such as inosine monophosphate, guanosine monophosphate, 1-octen-3-ol, and hexanal. These results offer insights into the distinctive meat quality and flavor compounds in WRMD2 during storage, providing fundamental data that could improve the management and quality of native chicken meat.